Social implications of human killings for money ritual among the Yoruba people of Southwestern Nigeria (2024)
Human killing for money ritual in Nigeria, particularly in the southwest region, has become a source of general concern. The highly valued virtues of hard work, honesty and dignity of labour have been sacrificed on the altar of materialism and the Get-Rich-Quick syndrome by the money ritualists. Their belief that wealth accumulation is more important regardless of the repercussions of such activities have negatively impacted the country's already fragile security situation. Over time, this menace has sparked a flurry of discussions among stakeholders on security issues related to development. Previous studies on the subject of money ritual induced human killing and its effects in southwest Nigeria has mostly been examined from a number of perspectives. Some scholars studied the problem from a security viewpoint, while others viewed it from the perspectives of poverty, greed, unemployment and loss of morals without paying adequate attention to its social implications. Therefore, the objective of this study is to examine the social implications of money ritual induced human killing. Youths and middle-aged men and women from Yoruba communities were interviewed using qualitative and unstructured questions. The findings showed that the causes of human killing for money ritual include greed, inordinate ambition, peer pressure, social media influence, poor parenting, loss of societal value systems, government insensitivity to the plight of the people, unemployment, corruption, and similar issues. The study recommends that both parents and government should make good efforts to reorient the youths as they also improve on security architectire.